Evaluation of a Double-Entry Turbine Model Coupled With a One-Dimensional Calibrated Engine Model at Engine Full Load Curves - Galindo, José; Serrano, José Ramón; De La Morena, Joaquín; Samala, Vishnu; Guilain, Stéphane; Batard, Samuel (Frontiers in Mechanical Engineering, 2021)
Turbocharging is one of the foremost ways of engine downsizing and represents the leading technology for reducing the engine CO2 emission standards in gasoline engine application. Turbocharger turbine always faces high unsteadiness of flow coming from the reciprocating internal combustion engines. Besides increasing levels of engine downsizing includes rising degrees of pulse charging. Utilization of pulse energy in the engine exhaust and reducing the interferences between the cylinders using the double-entry turbines is a vital element in solving the low-end-torque targets and improving rated power in highly boosted four-cylinder engines. The present paper describes a model of double-entry turbines. The model aim is to accommodate an efficient boundary condition to turbocharged engine models with zero and one-dimensional gas dynamic codes. The model is based on the simple procedure of testing and systematizing the performance maps of these turbines with different flow admission conditions. However, the described model in the present paper is capable of extrapolating operating conditions that differ from those included in the turbine maps. Because turbocharger turbine with an engine usually works instantaneously and away from the narrow range of data that are measured in the gas stand. The described model has been implemented in a one-dimensional gas dynamic code and has been used to calculate unsteady operating conditions coming from the engine. The results obtained from the whole engine simulation show that the model can produce all the full load engine variables like air mass flow and brake torque in a reasonable degree of agreement with the experimental data that are obtained from the engine test bench.